Usulan Sistem Persediaan Kasur Untuk Meminimasi Biaya Persediaan Total Dengan Batasan Gudang - Chandra, Hendry; Aritonang, Kinley (Jurnal Pendidikan Indonesia, 2025)
Aneka Jaya Store is a company in the furniture industry. It currently lacks a structured inventory system to manage demand, leading to intuitive and variable mattress ordering. This practice and limited warehouse space result in excess inventory and operational challenges. Consequently, the company seeks an enhanced inventory system to precisely define ordering intervals and quantities, aiming to minimize overall inventory costs. The proposed inventory management approach utilizes the T-method, the fixed order interval method, with a warehouse capacity constraint of 51 m3 for five designated products. This method mitigates stockouts by establishing order intervals (T) and maximum inventory quantities (M). Orders are placed based on the variance between the maximum inventory level and the remaining stock at the time of order placement. The T-Method employs both individual and joint ordering systems.The analysis reveals optimal order intervals and quantities after applying the individual and joint order T methods. For Export brands, joint orders are recommended every 17 days, with optimal amounts of 41 units for Export 120 and 40 units for Export 140. Teratai brand orders are bifurcated: individual orders for Teratai 90 products are suggested every 28 days with a supply of 26 units, while joint orders for Teratai 115 and Teratai 140 products are advised every 26 days, supplying 30 units and 27 units, respectively. Consequently, the total inventory cost for the five products amounts to IDR 15,992,603.49.